WALLABY Early Science – IV. ASKAP H i imaging of the nearby galaxy IC 5201. Issue 4 (26th July 2019) - Kleiner, D; Koribalski, B S; Serra, P; Whiting, M T; Westmeier, T; Wong, O I; Kamphuis, P; Popping, A; Bekiaris, G; Elagali, A; For, B-Q; Lee-Waddell, K; et al.
ABSTRACT: We present a Wide-field ASKAP L-Band Legacy All-sky Blind surveY (WALLABY) study of the nearby ( v sys = 915 km s −1 ) spiral galaxy IC 5201 using the Australian Square Kilometre Array Pathfinder (ASKAP). IC 5201 is a blue, barred spiral galaxy that follows the known scaling relations between stellar mass, SFR, H i mass, and diameter. We create a four-beam mosaicked H i image cube from 175 h of observations made with a 12-antenna sub-array. The root mean square noise level of the cube is 1.7 mJy beam −1 per channel, equivalent to a column density ofN_H I = 1.4 × 10 20 cm −2 over 25 km s −1 . We report nine extragalactic H i detections – five new H i detections including the first velocity measurements for two galaxies. These sources are IC 5201, three dwarf satellite galaxies, two galaxies, and a tidal feature belonging to the NGC 7232/3 triplet and two potential infalling galaxies to the triplet. There is evidence of a previous tidal interaction between IC 5201 and the irregular satellite AM 2220−460. A close fly-by is likely responsible for the asymmetric optical morphology of IC 5201 and warping its disc, resulting in the irregular morphology of AM 2220−460. We quantify the H i kinematics of IC 5201, presenting its rotation curve as well as showing that the warp starts at 14 kpc along the major axis, increasing as a function of radius with a maximum difference in position angle of 20°. There is no evidence of stripped H i, triggered or quenched star formation in the system as measured using DECam optical and GALEX UV photometry.